Analytical Potential of the In-Electrospray Ionization Source Hydrogen/Deuterium Exchange for the Investigation of Oligonucleotides. Issue 1 (February 2015) - Kostyukevich, Yury; Kononikhin, Alexey; Popov, Igor; Starodubtzeva, Natalia; Pekov, Stanislav; Kukaev, Eugene; Indeykina, Maria; Nikolaev, Eugene
It has previously been reported that different conformations of oligonucleotides may be detected using a gas-phase hydrogen/deuterium (H/D) exchange performed in the collision cell of a mass spectrometer. The presence of different conformers was postulated based on the bimodal shape of the deuterium distribution and on the ion mobility spectrometry data. Here we implement an in-electrospray ionization source H/D exchange to detect the different conformations of oligonucleotides in the region of ion formation. We observed that the number of H/D exchanges depends considerably on the temperature of the desolvating capillary and varies from 25% at 50°C to 80% at 450°C, but no bimodality in the shape of the deuterium distribution was observed. Such results indicate that in the region of ion formation different conformations of oligonucleotide ions rapidly interconvert one into another.